Health effects of occupational exposure to crystalline silica in the light of current research results - Aleksandra Maciejewska (Medycyna Pracy, 2014)
Crystalline silica is commonly found in the work environment. Possible health effects of occupational exposure continue to be the subject of extensive research. The aim of this paper was to analyze the recent findings concerning the health effects of exposure to crystalline silica, taking into account different levels of exposure. This work is based on the relevant information from the papers retrieved from the following databases: EBSCO, Scopus, ScienceDirect, and Web of Science, using the following keywords: crystalline silica, quartz, health effects. The review of the results confirms the multi-faceted harmful effects of crystalline silica. Prolonged occupational exposure, apart from silicosis and non-cancer respiratory diseases, may also result in the development of lung cancer, and autoimmune and chronic kidney diseases, the pathogenesis, which has not been completely explained yet. The exposure to the crystalline silica at concentrations close to the current occupational exposure limit value does not exclude the risk of the following pathologies: silicosis, lung cancer, other lung diseases and renal diseases. It is not feasible to completely eliminate the crystalline silica dust from the work environment. The best way to reduce the health effects of the exposure is to minimize the concentrations of silica dust. Further progress in clarifying the true mechanisms of interaction between silica dust and lung cells, the determination of the importance of surface properties of the silica particles in the pathogenic processes and explaining the effects of co-morbid dust in the work environment may help to prevent the harmful effects of silica dust. Med Pr 2014;65(6):799–818